Precedent Ideology and Judicial Legitimacy in Slovenia – An Outline - Tilen Štajnpihler Božič (Studia Iuridica Lublinensia, 2018)
Within the broader framework of the discussion of the potential of judicial precedent for statutory legal systems, this paper focuses on certain sociological aspects of the role a system of judicial precedent can have in the functioning of a judicial system. Proceeding specifically from the Slovenian legal context, the paper outlines the importance of openly and explicitly cultivating a commitment to a system of judicial precedent or unified and settled case-law in legal discourse, on the level of legal culture or ideology. It is argued that acknowledging the manner in which a system of judicial precedent can contribute to the rule of law has the potential to increase public trust and confidence in the judiciary and thus judicial legitimacy.